Managing customer attractiveness: How low-leverage customers mobilize critical supplier resources. Issue 2 (March 2022) - Kragh, Hanne; Ellegaard, Chris; Andersen, Poul Houman
Abstract : Getting access to the specialized resources of suppliers for purposes of innovation can be difficult especially for customers that are small or in other ways represent a limited immediate potential in the eyes of suppliers. Such low-leverage customers must find other ways of making themselves attractive to coveted suppliers. In this paper, we study how customers with low leverage manage the process of mobilizing supplier resources critical for innovation. We present findings from a single case study of a buying firm and show how they use five elements to gradually become attractive in the eyes of a critical supplier: proactive technological competence, canvassing and continuous communication, supplier learning, market access, and relationship maintenance. The different elements play different roles during the process of mobilizing supplier resources. We show that mobilizing suppliers in the case of low-leverage customers is a long-term process in which a number of interrelated attractiveness elements are leveraged in a complex pattern. This process is highly resource-demanding and requires substantial dedication and effort from the customer organization. Highlights: Supplier mobilization for innovation purposes is difficult for customers with low leverage. Customer attractiveness is an important part of supplier resource mobilization. Low-leverage customers gradually build attractiveness in the eyes of suppliers.